On soft σ-algebras - Khameneh, Azadeh Zahedi; Kilicman, Adem (Universiti Putra Malaysia Press, 2013)
The concept of soft sets, which was first introduced by Molodstov, is a new method to deal with uncertainty. In this work, we generalize probability theory to soft probability theory. We first introduce a soft σ-algebra as a collection of soft sets over an initial universe set X with a fixed set of parameters E and show the soft σ-algebra is a parameterized family of σ-algebras over X, then present some of its properties. Finally, we discuss on the soft probability space.